The Generic Alternative: Parodic Empowerment of Feminine Gothic Heroines in Margaret Atwood's Lady Oracle and The Handmaid's Tale - Rintoul, Suzanne (My University, 2003)
Margaret Atwood's Lady Oracle and The Handmaid's Tale are both parodies of the Feminine Gothic. However, little existing Atwood criticism explores this phenomenon in great detail, nor does it explore these two novels together in their mutual context. Moreover, although there has been a wealth of critical attention paid to Atwood's heroines' narrative subversions of phallocentric and Gothic expectation, there has been very little paid to its generic structure as a means of achieving the same end. This thesis proposes that Atwood empowers her heroines not only through narrative disruptions of Gothic and phallocentric systems, but also through the analogous structure of parody. Through enabling parodic analogies, Atwood's heroines become, like her readers, interpreters who are capable of negotiating and escaping the Gothic space.
Keywords: English Language and Literature; English Language and Literature